The Current Status of the Ketogenic Diet in Psychiatry - Bostock, Emmanuelle C. S.; Kirkby, Kenneth C.; Taylor, Bruce V. M. (Frontiers in Psychiatry, 2017)
Background The ketogenic diet (KD) has been used in treatment-resistant epilepsy since the 1920s. It has been researched in a variety of neurological conditions in both animal models and human trials. The aim of this review is to clarify the potential role of KD in psychiatry. Methods Narrative review of electronic databases PubMED, PsychINFO, and Scopus. Results The search yielded 15 studies that related the use of KD in mental disorders including anxiety, depression, bipolar disorder, schizophrenia, autism spectrum disorder (ASD), and attention deficit hyperactivity disorder (ADHD). These studies comprised nine animal models, four case studies, and two open-label studies in humans. In anxiety, exogenous ketone supplementation reduced anxiety-related behaviors in a rat model. In depression, KD significantly reduced depression-like behaviors in rat and mice models in two controlled studies. In bipolar disorder, one case study reported a reduction in symptomatology, while a second case study reported no improvement. In schizophrenia, an open-label study in female patients (n = 10) reported reduced symptoms after 2 weeks of KD, a single case study reported no improvement. In a brief report, 3 weeks of KD in a mouse model normalized pathological behaviors. In ASD, an open-label study in children (n = 30) reported no significant improvement; one case study reported a pronounced and sustained response to KD. In ASD, in four controlled animal studies, KD significantly reduced ASD-related behaviors in mice and rats. In ADHD, in one controlled trial of KD in dogs with comorbid epilepsy, both conditions significantly improved. Conclusion Despite its long history in neurology, the role of KD in mental disorders is unclear. Half of the published studies are based on animal models of mental disorders with limited generalizability to the analog conditions in humans. The review lists some major limitations including the lack of measuring ketone levels in four studies and the issue of compliance to the rigid diet in humans. Currently, there is insufficient evidence for the use of KD in mental disorders, and it is not a recommended treatment option. Future research should include long-term, prospective, randomized, placebo-controlled crossover dietary trials to examine the effect of KD in various mental disorders.